ПОЭЗИЯҒА ӨЗЕК БОЛҒАН «ХАЛЫҚ СӨЗЛЕРИ» - Баўатдинова, С. (ILIM hám JÁMIYET, 2021)
The article depicts the roots of becoming folk poems and relation of folk with I.Yusupov’s poem «Khalk so’zlari» (People’s words). Proverbs and sayiugs which used poet in his works transformed and in balance with original version recreated. With combination of poetic devices made the great composition.